2009
DOI: 10.1523/jneurosci.1746-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Glt1 Attenuates Cue-Induced Reinstatement of Cocaine-Seeking Behavior in Rats

Abstract: Relapse to cocaine-seeking behavior depends on increased glutamate transmission in key regions of the mesocorticolimbic motive circuit, including prefrontal cortex (PFC) and nucleus accumbens (NAcc). Because GLT1 is responsible for the uptake of Ն90% of extracellular glutamate, we tested the hypothesis that increased GLT1 expression attenuates cocaine relapse. Rats were trained to selfadminister cocaine (0.125 mg per intravenous infusion) in a lever-pressing task in a daily 2 h session for 10 -14 d followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
198
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(212 citation statements)
references
References 44 publications
11
198
3
Order By: Relevance
“…The murine EAAT2 (Slc1a2) gene is located in a central part of chromosome 2 (E2) (Kirschner et al, 1994), near quantitative trait loci that modulate neuroexcitability and seizure frequency in mouse models of alcohol withdrawal and epilepsy (Crabbe and Belknap, 1993). EAAT2 is also implicated in preclinical models of morphine, methamphetamine, and cocaine addiction (Abulseoud et al, 2012;Sari et al, 2009). Moreover, it is noteworthy that genetic polymorphisms of EAAT2 have been linked to alcoholism in humans (Sander et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The murine EAAT2 (Slc1a2) gene is located in a central part of chromosome 2 (E2) (Kirschner et al, 1994), near quantitative trait loci that modulate neuroexcitability and seizure frequency in mouse models of alcohol withdrawal and epilepsy (Crabbe and Belknap, 1993). EAAT2 is also implicated in preclinical models of morphine, methamphetamine, and cocaine addiction (Abulseoud et al, 2012;Sari et al, 2009). Moreover, it is noteworthy that genetic polymorphisms of EAAT2 have been linked to alcoholism in humans (Sander et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, sensitization studies revealed a deficit in basal glutamate levels in the nucleus accumbens that was confirmed in animals with a history of cocaine self-administration. This led to experiments demonstrating that restoring basal glutamate levels in the nucleus accumbens could reduce relapse to drug-seeking behavior in animal models and humans (Baker et al, 2003;Mardikian et al, 2007;Zhou and Kalivas, 2008;Knackstedt et al, 2009Knackstedt et al, , 2010Sari et al, 2009). This type of progression from studies with behavioral sensitization to validation using models of reinstated drug-seeking and to clinical trials is especially useful to consider for potential pharmacotherapeutic targets identified from genomic and proteomic screens, which do not provide a priori evidence for the involvement of a drug-induced change in addiction.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Moreover, GLT-1-overexpressing mice show a significant reduction in disease severity following pilocarpine-induced SE , suggesting that targeting glutamate transporters through transcriptional or translational regulation processes could represent an as-yet untapped therapeutic strategy for excitotoxic injury, including epilepsy . Efforts are now underway to use ceftriaxone to increase expression of glutamate transporters in a variety of preclinical models and clinical disorders associated with glutamate-mediated excitotoxic injury, including ALS (Simantov et al 1999;Berry et al 2013), Huntington's disease (Miller et al 2008), substance-abuse disorders (Sari et al 2009;Abulseoud et al 2012), traumatic brain injury (Goodrich et al 2013), and epilepsy (Jelenkovic et al 2008;Rawls et al 2010;Zeng et al 2010). As interest in, and understanding of, glial function in pathological conditions grows, efforts to capitalize on this knowledge will provide significant potential for "glia-centric" therapeutics.…”
Section: A Role For Glial Regulation Of Glutamate In Epilepsymentioning
confidence: 99%